2012
DOI: 10.1590/s1677-55382012000500012
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of urethral mobility and valsalva leak point pressure for female transobturator sling procedure

Abstract: ARTICLE INFO _________________________________________________________ ___________________Purpose: To analyze the influence of urethral mobility and Valsalva leak point pressure on postoperative outcomes of transobturator sling (TOT) for female stress urinary incontinence. Materials and Methods: A prospective cohort was conducted including 66 patients submitted to TOT from March 2006 to May 2009. Urethral hypermobility was defined as mobility ≥ 30º on Q-tip test, and Valsalva leak point pressure (VLPP) was cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 23 publications
2
11
0
Order By: Relevance
“…Similar to earlier studies, we found that urethral mobility plays an important role in surgical outcomes following vaginal tape insertion procedures . For women with a hypermobile urethra—one of the main indications for treatment with a TOT—the likelihood of success is generally high.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Similar to earlier studies, we found that urethral mobility plays an important role in surgical outcomes following vaginal tape insertion procedures . For women with a hypermobile urethra—one of the main indications for treatment with a TOT—the likelihood of success is generally high.…”
Section: Discussionsupporting
confidence: 87%
“…Our findings show that when inserting a TOT, beginning the incision at 1/2 the urethral length was more likely to result in a successful outcome than at 1/3 of the urethral length—similar to the standard technique for classical retropubic TVT . One important conclusion of this study, which is consistent with earlier studies, is that patient characteristics (i.e., urethral mobility) ought to be assessed and appropriately matched with the particular functionality of the tapes …”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…A small number of patients in our study is thought to have prevented the net effect of menopausal status on the outcomes after the TOT procedure to become apparent. There are reports indicating that advanced age could negatively affect the success rate of the TOT procedure [23,24]. In contrast, de Toledo et al reported that patient age did not affect the outcomes of the TOT procedure [24].…”
Section: Discussionmentioning
confidence: 99%
“…There are reports indicating that advanced age could negatively affect the success rate of the TOT procedure [23,24]. In contrast, de Toledo et al reported that patient age did not affect the outcomes of the TOT procedure [24]. In our study, we did not find any difference between patients below and at or above 50 years of age in terms of treatment success and complication rates, a finding which is in conformity with that in the study by de Toledo et al (p = 0.351 and p = 1.000, respectively).…”
Section: Discussionmentioning
confidence: 99%